Assessment of the Root Canal Similarity in Contralateral Mandibular Incisors - Gaute Floer Johnsen; Håvard Haugen, J; Liebert Parreiras Nogueira; Usame Sevgi; Ashley Mae Jimenez; Joseph T. DeLuca; Ryan Mancuso; Lucila Piasecki (Elsevier, 2023)
Introduction: The purpose of this study was to determine the degree of similarity between contralateral mandibular incisors utilising 3-dimensional (3D) models obtained from micro-computed tomographic (micro-CT) scans of extracted human teeth. The null hypothesis was that contralateral mandibular incisors do not exhibit matching symmetry. Methods: Sixty pairs (n = 120) of extracted mandibular incisors were obtained from 30 patients and scanned with micro-CT with a voxel size of 15.0 μm. 3D virtual models of the pulpal cavities were rendered. Geometric morphometric deviation analysis was performed after mirroring, automatic alignment, and co-registration of the models of contralateral teeth root mean square (RMS) errors were calculated. The quantitative analysis of the 3D models included 6 different geometric parameters. Data sets were examined with a 2-sample Kolmogorov-Smirnov test. Post hoc retrospective power analysis was performed to find statistical power (α = 0.05). Results: Contralateral pairs had a narrower distribution in deviation than random pairs. Also, contralateral pairs showed a statistically higher similarity coefficient (5 out of 6 geometric parameters) compared to random pairs (P < .001); no difference was found when comparing central to lateral pairs or between Vertucci type I configurations compared to non-type I. RMS errors had significantly lower Contralateral premolars (CPs) values than random pairs (P < .001). Conclusions: A high degree of similarity was demonstrated for pairing contralateral mandibular incisors using 3D models. The similarity between contralateral central and lateral incisors suggests that when screened and matched, these 4 teeth might be used in endodontic research where similar root canal anatomy is crucial.